If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 90 + -4x = 23x + 21 Reorder the terms: 90 + -4x = 21 + 23x Solving 90 + -4x = 21 + 23x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-23x' to each side of the equation. 90 + -4x + -23x = 21 + 23x + -23x Combine like terms: -4x + -23x = -27x 90 + -27x = 21 + 23x + -23x Combine like terms: 23x + -23x = 0 90 + -27x = 21 + 0 90 + -27x = 21 Add '-90' to each side of the equation. 90 + -90 + -27x = 21 + -90 Combine like terms: 90 + -90 = 0 0 + -27x = 21 + -90 -27x = 21 + -90 Combine like terms: 21 + -90 = -69 -27x = -69 Divide each side by '-27'. x = 2.555555556 Simplifying x = 2.555555556
| 9x+15=96 | | -4x-23x=21-90 | | 0.24(24)+0.03x=0.09(18+x) | | (3y^4+4)-3y^4=0 | | 2X+21=5X | | (11a^3+6)-(-7a^3+12)=0 | | -10x+38x=143-7 | | 14x+12=110 | | -6x+4-7x=134 | | -7z^6-(-2z^6-3)=0 | | 7u^2-(2u^2-8)=0 | | 9x-7y=66 | | (13x^7-6)-(-14x^7+11)=0 | | -6+4-7x=134 | | (13x^7-6)-(14x^7+11)=0 | | 4x^2+5x-6=y | | -4=x-2x+6 | | (-10x^8-14)-12x^8=0 | | (13z^9+6v)-11z^9=0 | | 2x-9x+6=7x-20 | | 12+6b=2b-4 | | (-8y^5+4)-(13y^5-6)=0 | | (-3y^9+15)-9y^9=0 | | 18x^2-15x=7 | | 4w^2-(-15w^2-15)=0 | | 64x^2-128x+64x=9 | | 3y-3=10x-10 | | (-13y^9+6)-(-4y^9)=0 | | x-10=2x-34 | | 4x-9x=13-63 | | 3(5x-6)=42 | | 7x+6=-5x |